Pelaksanaan Identifikasi Pasien Terhadap Pencegahan Kesalahan Dalam Pemberian Obat di RSUD Otanaha Kota Gorontalo - Sabirin B. Syukur; Windrawati ismail (Termometer: Jurnal Ilmiah Ilmu Kesehatan dan Kedokteran, 2023)
Introduction: Patient identification is helpful to ensure that patients receive the necessary level of care and are appropriate according to their medical needs. In addition, patient identification can help prevent the occurrence of medical errors or other unforeseen circumstances that can negatively affect the patient. Purpose: To conduct an analysis of the Implementation of Patient Identification of Prevention of Errors in Medication Administration. Research Methods: this type of observational and descriptive research. The subjects of this study were nurses. Research results: from the implementation of patient identification there are 4 identifications that are still often not carried out namely Saying greetings Not Carrying Out 67%, Mentioning names and what Not Carrying Out 78%. Ask the patient/patient's family to state the name of the patient. Not Implementing 11%. Say thank you Don't Implement 67%. But in administering the drug there were no errors: Conclusion: that there are still nurses who do not carry out all the standard patient identification procedures. Suggestion: nurses identify patients when administering drugs so that they can carry out all stages of identification according to the SOP that has been provided.